Knowledge management tools of rice technology in Nepal - Tripathi, BP (Agronomy Journal of Nepal, 2013)
Technology plays an important role for enhancing production and productivity. In Nepal, the apex research body, Nepal Agricultural Research council (NARC) is mandated for generating technology whereas Department of Agriculture Extension is responsible for disseminating rice technologies to the farmers’ fields through different channels of the system. Different International and National Non-Government Organization (INGOs/NGOs) are also involved in dissemination of rice technologies as well. Although technologies are disseminating however, adoption rate of rice seems to be low. Awareness is an issue to adopt the right technology. Knowledge Management Tools (KMT) followed for rice in Nepal are fact sheets, farmers’ field school, printed media, radio, television, toll free services, training and visit, and mini-kit distribution. Therefore, to find out the gap between adoption and disseminating technology, a study on KMT was carried out. Informant survey was launched to collect the data covering four regions of Nepal taking 2 districts in each region during 2010. Mini-kit distribution to the farmers, technologies through farmers’ group and training to the farmers were the most effective for transferring rice technologies, which were confirmed by 49 (62.9%), 46 (59.0%) and 41 (52.8%) interviewed farmers, respectively. Among the electronic media, FM radio and radio were most effective tools for disseminating rice technologies, which were shown by 33 (42.3%) and 23 (29.5%) farmers respectively. Among the printed media, booklet and news paper were most effective for transferring rice technologies as confirmed by 21 (27.0%) and 13 (16.7%) farmers respectively. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7518 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.24-30